2005
DOI: 10.4049/jimmunol.174.7.4210
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between CD14 and Complement Receptor 3 Promotes Phagocytosis of Mycobacteria: Regulation by Phosphatidylinositol 3-Kinase and Cytohesin-1

Abstract: The glycosylphosphatidyl anchored molecule CD14 to the monocyte membrane plays a prominent role in innate immunity, and the paradigms for CD14 selective signaling are beginning to be elucidated. In this study, transfected human monocytic cell line THP-1 and Chinese hamster ovary (CHO) fibroblastic cells were used to examine phagocytosis of Mycobacterium bovis bacillus Calmette-Guérin (BCG). Flow cytometry was combined with molecular and biochemical approaches to demonstrate a dual mechanism for BCG internaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
91
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 67 publications
(63 reference statements)
4
91
1
1
Order By: Relevance
“…Our initial report that P. gingivalis fimbriae stimulate TLR2 inside-out signaling for CR3 activation was published concomitantly with a study by an independent group which showed that mycobacterial lipoarabinomannan also activates this proadhesive pathway (Sendide et al, 2005). Strikingly, mycobacteria exploit the TLR2/ CR3 pathway for promoting their entry into monocytes/macrophages (Sendide et al, 2005) where they can parasitize (Ernst, 1998).…”
Section: P Gingivalis Enters Macrophages Via Cr3 and Resists Intracementioning
confidence: 98%
See 1 more Smart Citation
“…Our initial report that P. gingivalis fimbriae stimulate TLR2 inside-out signaling for CR3 activation was published concomitantly with a study by an independent group which showed that mycobacterial lipoarabinomannan also activates this proadhesive pathway (Sendide et al, 2005). Strikingly, mycobacteria exploit the TLR2/ CR3 pathway for promoting their entry into monocytes/macrophages (Sendide et al, 2005) where they can parasitize (Ernst, 1998).…”
Section: P Gingivalis Enters Macrophages Via Cr3 and Resists Intracementioning
confidence: 98%
“…Strikingly, mycobacteria exploit the TLR2/ CR3 pathway for promoting their entry into monocytes/macrophages (Sendide et al, 2005) where they can parasitize (Ernst, 1998). The potential for CR3 exploitation by certain pathogens may, at least partly, be related to the notion that CR3 is not linked to vigorous microbicidal mechanisms, in contrast to most phagocytic receptors (Lowell, 2006;Wright and Silverstein, 1983;Yamamoto and Johnston, 1984;Caron and Hall, 1998;Rosenberger and Finlay, 2003).…”
Section: P Gingivalis Enters Macrophages Via Cr3 and Resists Intracementioning
confidence: 99%
“…Further, the GEF for ARF-GTPase, cytohesin-1, is involved in CD14/TLR2-mediated phagocytosis of mycobacteria by human macrophages. Knockdown of cytohesin-1 resulted in a marked attenuation of phagocytosis of mycobacteria (22).…”
Section: Discussionmentioning
confidence: 98%
“…However, we have not yet determined whether experimental addition of sCD14, or chimerism devised by delivery of congenic CD14-expressing phagocytes, can modulate MSU crystal-induced inflammation of air pouches in the CD14-deficient mouse. Last, MSU crystals engage the integrin CD11b/CD18, and engagement of CD11b/CD18 and phagocyte activation by certain bacterial products are mediated by complex formation of CD14, TLR2, and CD11b/CD18 (28). Hence, it is conceivable that the role of CD14 in MSU crystal-induced inflammation is primarily via macromolecular complex formation with TLRs and integrins that are directly responsible for modulating cellular responsiveness to MSU crystals.…”
Section: Discussionmentioning
confidence: 99%
“…CD14 lacks both transmembrane and intracellular domains. However, the association of CD14 with other plasma membrane molecules, including formation of cell surface complexes of CD14 with TLR2, TLR4 (22,23), and certain integrins and FcR (28,29) provide the means for CD14 to modulate signal transduction.…”
mentioning
confidence: 99%